LncRNA LBX2-AS1 inhibits acute myeloid leukemia progression through miR-455-5p/MYLIP axis - Gongli Fu; Hao Wu; Xiaomiao Wu; Yang Yang; Cuihua Fan (Heliyon, 2024)
Acute myeloid leukemia (AML) is a common blood cancer primarily affecting the bone marrow and blood cells, which is prevalent among adults. Long non-coding RNAs (lncRNAs) have been shown to play a crucial role in the development and progression of AML. LBX2-AS1 is a recently discovered lncRNA that has been linked to the pathogenesis and progression of several types of cancer. This study aimed to investigate the role and possible mechanisms of LBX2-AS1 in AML. Expression levels of LBX2-AS1, miR-455-5p, and their target genes were detected in AML samples and cells by RT-qPCR. Cell proliferation and apoptosis were determined by Cell Counting Kit-8 and 5-ethynyl-2′-deoxyuridine assays, and flow cytometry, respectively. LBX2-AS1 was downregulated in AML specimens and cells, and overexpression of LBX2-AS1 significantly inhibited cell proliferation and enhanced apoptosis in vitro. We also determined the effects of LBX2-AS1 overexpression in an AML mouse model by in vivo bioluminescence imaging. Mechanistically, LBX2-AS1 acts as a competitive endogenous RNA, which promotes myosin regulatory light chain interacting protein (MYLIP) expression by sponging miR-455-5p. Knockdown of MYLIP or upregulation of miR-455-5p antagonized the effect of LBX2-AS1 overexpression on the progression of AML. LBX2-AS1 may thus be a valuable therapeutic target for AML.